Impact of the COVID-19 pandemic on the self-care and health condition of the older adults. CUIDAMOS+75. A mixed methods study protocol - Rico-Blazquez, Milagros; Esteban-Sepúlveda, Silvia; Sánchez-Ruano, Raquel; Aritztegui-Echenique, Ana María; Artigues-Barbera, Eva María; Brito-Brito, Pedro Ruymán; Casado-Ramirez, Elvira; Cidoncha-Moreno, María Ángeles; Fabregat-Julve, María Inmaculada; Feria-Raposo, Isabel; Hernandez-Pascual, Montserrat; Lozano-Hernández, Cristina; et al. (Frontiers in Public Health, 2024)
Aims To assess the impact of the COVID-19 pandemic on the health condition of people ≥75 years of age and on their family caregivers in Spain. Design Multicentric, mixed method concurrent study. Methods This work, which will be conducted within the primary care setting in 11 administrative regions of Spain, will include three coordinated studies with different methodologies. The first is a population-based cohort study that will use real-life data to analyze the rates and evolution of health needs, care provision, and services utilization before, during, and after the pandemic. The second is a prospective cohort study with 18 months of follow-up that will evaluate the impact of COVID-19 disease on mortality, frailty, functional and cognitive capacity, and quality of life of the participants. Finally, the third will be a qualitative study with a critical social approach to understand and interpret the social, political, and economic dimensions associated with the use of health services during the pandemic. We have followed the SPIRIT Checklist to address trial protocol and related documents. This research is being funded by the Instituto de Salud Carlos III since 2021 and was approved by its ethics committee (June 2022). Discussion The study findings will reveal the long-term impact of the COVID-19 pandemic on the older adults and their caregivers. This information will serve policymakers to adapt health policies to the needs of this population in situations of maximum stress, such as that produced by the COVID-19 pandemic. Trial Registration Identifier: NCT05249868 [ClinicalTrials.gov].